Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's evaluate the given integrals step-by-step.
### (a) [tex]\(\int \cos^3 \theta \, d\theta\)[/tex]
To begin, we need to express [tex]\(\cos^3 \theta\)[/tex] in a form that is easier to integrate. We can use the trigonometric identity:
[tex]\[ \cos^3 \theta = \cos \theta \cdot \cos^2 \theta \][/tex]
and we can rewrite [tex]\(\cos^2 \theta\)[/tex] using the identity [tex]\(\cos^2 \theta = 1 - \sin^2 \theta\)[/tex]:
[tex]\[ \cos^3 \theta = \cos \theta \cdot (1 - \sin^2 \theta) = \cos \theta - \cos \theta \cdot \sin^2 \theta \][/tex]
Now, we can break this into two separate integrals:
[tex]\[ \int \cos^3 \theta \, d\theta = \int (\cos \theta - \cos \theta \cdot \sin^2 \theta) \, d\theta \][/tex]
We can split the integral:
[tex]\[ \int \cos^3 \theta \, d\theta = \int \cos \theta \, d\theta - \int \cos \theta \cdot \sin^2 \theta \, d\theta \][/tex]
The first integral is straightforward:
[tex]\[ \int \cos \theta \, d\theta = \sin \theta \][/tex]
For the second integral, let's use the substitution [tex]\( u = \sin \theta \)[/tex]. Then [tex]\( du = \cos \theta \, d\theta \)[/tex]:
[tex]\[ \int \cos \theta \cdot \sin^2 \theta \, d\theta = \int \sin^2 \theta \, du = \int u^2 \, du \][/tex]
Integrating [tex]\( u^2 \)[/tex]:
[tex]\[ \int u^2 \, du = \frac{u^3}{3} + C = \frac{\sin^3 \theta}{3} + C \][/tex]
Combining these results, we have:
[tex]\[ \int \cos^3 \theta \, d\theta = \sin \theta - \frac{\sin^3 \theta}{3} + C \][/tex]
So, the result is:
[tex]\[ \int \cos^3 \theta \, d\theta = -\frac{\sin^3 \theta}{3} + \sin \theta + C \][/tex]
### (b) [tex]\(\int \frac{\ln \left(x^2\right)}{x^2} \, dx\)[/tex]
First, simplify the integrand using the property of logarithms:
[tex]\[ \ln(x^2) = 2 \ln(x) \][/tex]
So the integral becomes:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = \int \frac{2 \ln(x)}{x^2} \, dx = 2 \int \frac{\ln(x)}{x^2} \, dx \][/tex]
Let's use the substitution [tex]\( u = \ln(x) \)[/tex]. Then [tex]\( du = \frac{1}{x} \, dx \)[/tex], which implies [tex]\( dx = x \, du \)[/tex]:
[tex]\[ 2 \int \frac{\ln(x)}{x^2} \, dx = 2 \int \frac{u}{x} \cdot \frac{1}{x} \, dx = 2 \int \frac{u}{x^2} \cdot x \, du = 2 \int \frac{u}{x} \cdot x \, du \][/tex]
Since [tex]\( x \, du = dx \)[/tex], we have:
[tex]\[ 2 \int u \cdot \frac{du}{x} = 2 \int u \cdot \frac{du}{x} \][/tex]
Given [tex]\( x = e^u \)[/tex], we get [tex]\( \frac{du}{x} = e^{-u} \, du \)[/tex]:
[tex]\[ 2 \int u \cdot e^{-u} \, du \][/tex]
Integrate by parts, taking [tex]\( v = u \)[/tex] and [tex]\( dw = e^{-u} \, du \)[/tex]:
[tex]\[ dv = du \text{ and } w = -e^{-u} \][/tex]
Applying the integration by parts formula [tex]\( \int v \, dw = vw - \int w \, dv \)[/tex]:
[tex]\[ 2 \int u \cdot e^{-u} \, du = 2 \left( -u e^{-u} - \int -e^{-u} \, du \right) = 2 \left( -u e^{-u} + e^{-u} \right) = 2 \left( \frac{-\ln(x)}{x} + \frac{1}{x} \right) \][/tex]
So, the integral is:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = 2 \left( -\frac{\ln(x)}{x} + \frac{1}{x} \right) + C = \frac{-2 \ln(x)}{x} + \frac{2}{x} + C \][/tex]
Thus, the final answer is:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = -\frac{\ln(x^2)}{x} - \frac{2}{x} + C \][/tex]
### (a) [tex]\(\int \cos^3 \theta \, d\theta\)[/tex]
To begin, we need to express [tex]\(\cos^3 \theta\)[/tex] in a form that is easier to integrate. We can use the trigonometric identity:
[tex]\[ \cos^3 \theta = \cos \theta \cdot \cos^2 \theta \][/tex]
and we can rewrite [tex]\(\cos^2 \theta\)[/tex] using the identity [tex]\(\cos^2 \theta = 1 - \sin^2 \theta\)[/tex]:
[tex]\[ \cos^3 \theta = \cos \theta \cdot (1 - \sin^2 \theta) = \cos \theta - \cos \theta \cdot \sin^2 \theta \][/tex]
Now, we can break this into two separate integrals:
[tex]\[ \int \cos^3 \theta \, d\theta = \int (\cos \theta - \cos \theta \cdot \sin^2 \theta) \, d\theta \][/tex]
We can split the integral:
[tex]\[ \int \cos^3 \theta \, d\theta = \int \cos \theta \, d\theta - \int \cos \theta \cdot \sin^2 \theta \, d\theta \][/tex]
The first integral is straightforward:
[tex]\[ \int \cos \theta \, d\theta = \sin \theta \][/tex]
For the second integral, let's use the substitution [tex]\( u = \sin \theta \)[/tex]. Then [tex]\( du = \cos \theta \, d\theta \)[/tex]:
[tex]\[ \int \cos \theta \cdot \sin^2 \theta \, d\theta = \int \sin^2 \theta \, du = \int u^2 \, du \][/tex]
Integrating [tex]\( u^2 \)[/tex]:
[tex]\[ \int u^2 \, du = \frac{u^3}{3} + C = \frac{\sin^3 \theta}{3} + C \][/tex]
Combining these results, we have:
[tex]\[ \int \cos^3 \theta \, d\theta = \sin \theta - \frac{\sin^3 \theta}{3} + C \][/tex]
So, the result is:
[tex]\[ \int \cos^3 \theta \, d\theta = -\frac{\sin^3 \theta}{3} + \sin \theta + C \][/tex]
### (b) [tex]\(\int \frac{\ln \left(x^2\right)}{x^2} \, dx\)[/tex]
First, simplify the integrand using the property of logarithms:
[tex]\[ \ln(x^2) = 2 \ln(x) \][/tex]
So the integral becomes:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = \int \frac{2 \ln(x)}{x^2} \, dx = 2 \int \frac{\ln(x)}{x^2} \, dx \][/tex]
Let's use the substitution [tex]\( u = \ln(x) \)[/tex]. Then [tex]\( du = \frac{1}{x} \, dx \)[/tex], which implies [tex]\( dx = x \, du \)[/tex]:
[tex]\[ 2 \int \frac{\ln(x)}{x^2} \, dx = 2 \int \frac{u}{x} \cdot \frac{1}{x} \, dx = 2 \int \frac{u}{x^2} \cdot x \, du = 2 \int \frac{u}{x} \cdot x \, du \][/tex]
Since [tex]\( x \, du = dx \)[/tex], we have:
[tex]\[ 2 \int u \cdot \frac{du}{x} = 2 \int u \cdot \frac{du}{x} \][/tex]
Given [tex]\( x = e^u \)[/tex], we get [tex]\( \frac{du}{x} = e^{-u} \, du \)[/tex]:
[tex]\[ 2 \int u \cdot e^{-u} \, du \][/tex]
Integrate by parts, taking [tex]\( v = u \)[/tex] and [tex]\( dw = e^{-u} \, du \)[/tex]:
[tex]\[ dv = du \text{ and } w = -e^{-u} \][/tex]
Applying the integration by parts formula [tex]\( \int v \, dw = vw - \int w \, dv \)[/tex]:
[tex]\[ 2 \int u \cdot e^{-u} \, du = 2 \left( -u e^{-u} - \int -e^{-u} \, du \right) = 2 \left( -u e^{-u} + e^{-u} \right) = 2 \left( \frac{-\ln(x)}{x} + \frac{1}{x} \right) \][/tex]
So, the integral is:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = 2 \left( -\frac{\ln(x)}{x} + \frac{1}{x} \right) + C = \frac{-2 \ln(x)}{x} + \frac{2}{x} + C \][/tex]
Thus, the final answer is:
[tex]\[ \int \frac{\ln(x^2)}{x^2} \, dx = -\frac{\ln(x^2)}{x} - \frac{2}{x} + C \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.